The social cost of carbon and inequality: when local redistribution shapes global carbon prices - Kornek, Ulrike; Klenert, David; Edenhofer, Ottmar; Fleurbaey, Marc (Munich, 2019)
"The social cost of carbon is the central economic measure for aggregate climate change damages and functions as a metric for optimal carbon prices. Previous literature shows that inequality significantly influences the level of the social cost of carbon, but mostly neglects a major source of inequality - heterogeneity in income below the national level. We characterize the relationship between climate and redistributional policy in an optimal taxation model that explicitly accounts for inequality between and within countries. In particular, we demonstrate that climate and distributional policy cannot be separated when national governments fail to compensate low-income households for climate change damages: Even if only one country does not compensate especially affected households, the social cost of carbon increases globally. Further, we use numerical methods to estimate the scope of these effects. Our results suggest that it is crucial to correct previous estimates of the social cost of carbon for national distributional policies."